Commercial silage additive trials - K. Bolsen (Kansas Agricultural Experiment Station Research Reports, 1981)
Most Kansas grown crops can be harvested, stored, and fed as silage. A good silage fermentation should produce a well-preserved, palatable feed with minimum nutrient loss, but making a good silage requires good management. The crop must be harvested at the proper maturity and moisture, be finely chopped, and be tightly packed in the silo. Numerous commercial silage additives, whose manufacturers make various claims for improving silage quality, are available. Last year, we reported on 5 trials involving six commercial additives (Report of Progress 377). Each additive improved the silage in at least one of the four criteria we evaluate.
Keywords: Cattlemen' s Day; 1981; Report of progress (Kansas State University. Agricultural Experiment Station); 394; Beef; Silage